Scoping review of the hardware and software features of virtual reality exposure therapy for social anxiety disorder, agoraphobia, and specific phobia - Arnfred, Benjamin; Svendsen, Johanna Kvist; Adjourlu, Ali; Horthøj, Carsten (Frontiers in Virtual Reality, 2023)
The use of virtual reality technology to deliver exposure therapy in the treatment of phobic anxiety (i.e. social anxiety disorder, agoraphobia, and specific phobia) has been proposed to be advantageous compared with in-vivo exposure therapy. These supposed advantages depend on the features of the virtual reality technology and how it is used therapeutically. Therefore, the aim of this study was to provide a comprehensive overview of the features of the hardware and software used in studies examining virtual reality exposure therapy studies for phobic anxiety disorders. 70 studies using virtual reality exposure therapy to treat social anxiety disorder, agoraphobia and/or specific phobia, were systematically reviewed for 46 data points relating to these features. We found that studies generally did not utilize contemporary virtual reality technology and that hardware and software features were inconsistently delineated. Implications of this are discussed and a preliminary framework for reporting technical features of virtual reality exposure interventions is proposed.